Using "Salowis-App" to Improve Class 7 Students' Interest in Learning Science Physics in Measurement Materials - Rizky Merian Muspa; Fitri Nurhayati; Syifa Alkautsar (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2023)
Â Students' interest in learning decreased after the Covid-19 Pandemic when face-to-face learning was carried out, this was marked by students experiencing a decrease in the ability to ask questions, lack of confidence when asked by the teacher, and when repeating the scores obtained under the minimum completeness criteria. The purpose of this research is to develop online learning media that is able to improve the level of interest in learning Science Physics for grade 7 junior high school students in measurement materials using the SaLoWis-App. The developed application can be applied to gadgets/smartphones by loading local wisdom content in Berbah so that it is more real for students to know. The research method used is the development model. The SaLoWis-App application was developed through a combination of several Google Workspace services such as Google Sites, Google Slides, and Google Forms which were optimized by Canva to make the design more attractive. The instrument used was questionnaires via Google Forms to assess student satisfaction regarding aspects of learning, media, and media design as an illustration of their level of interest in learning using the SaLoWis-App. The results of the research obtained an average value of each aspect sequentially, namely the learning aspect at 4.59 (Very Good), media at 4.49 (Good), and design at 4.58 (Very Good). With this value, it is concluded that students have satisfaction with learning using the online media SaLoWis-App for measurement material in grade 7 junior high school so it has a positive impact on increasing student interest in learning.